Keeping Gunpowder Unlawfully, The Penal Code of the State of Minnesota, § 323 (1885). - (:unkn) unknown (General Publisher, 1885)
A person who makes, or keeps, gunpowder, nitro-glycerine, or any other explosive or combustible material, within a city or village, or carries such materials through the streets thereof, in a quantity or manner prohibited by law, or by ordinance of the city or village, is guilty of a misdemeanor. And a person who, by the careless, negligent or unauthorized use or management of gunpowder or other explosive substance, injures, or occasions the injury of, the person or property of another, is punishable by imprisonment in the county jail for not more than one (1) year."
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER